Analysis of X-COMP in Periphrastic Causative Constructions: The Case of the Duri Dialect in the Massenrempulu Language - Fathonah, Siti; Kumalasari, Rita (CV. Tripe Konsultan, 2024)
Periphrastic causative constructions elucidate the causal relationship between two actions inside a single event. The periphrastic causative construction includes X-COMP in the subordinate sentence. This research on X-COMP in the Massenrempulu language employs a descriptive methodology. Data sources derive from written and spoken speech, particularly those featuring the X-COMP form. Data gathering was executed using reading, note-taking, and interviewing methodologies. The employed data analysis method is qualitative descriptive analysis. The causal periphrasis structure in the Duri dialect of the Massenrempulu language is constituted by the verbs kuanni and mangkabua. X-COMP in the causal periphrastic construction of the Massenrempulu language has traits similar to X-COMP in other global languages. The attributes of X-COMP in the Massenrempulu language are contingent upon the subject or object of the principal clause and the existence of the verb that constitutes the causal construction within the principal clause.